If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x+2/3-(1/2) = x/3-((2*(x-2))/3) // - x/3-((2*(x-2))/3)
(2*(x-2))/3+x-(x/3)+2/3-(1/2) = 0
(2*(x-2))/3+x-(x/3)+2/3-1/2 = 0
(2*(x-2))/3+x-x/3+2/3-1/2 = 0
(2^2*(x-2))/(2*3)+(2*3*x)/(2*3)+(2*(-x))/(2*3)+(2^2)/(2*3)+(-1*3)/(2*3) = 0
2^2*(x-2)+2*3*x+2*(-x)-1*3+4 = 0
10*x-2*x-8-3+4 = 0
8*x-8-3+4 = 0
8*x-4-3 = 0
8*x-7 = 0
(8*x-7)/(2*3) = 0
(8*x-7)/(2*3) = 0 // * 2*3
8*x-7 = 0
8*x-7 = 0 // + 7
8*x = 7 // : 8
x = 7/8
x = 7/8
| -3x-3(-5x-17)=17 | | -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x | | 5/10+7/3 | | (2x-3)(x^3-x^2+3x+5)=0 | | 2x-2x+3=8 | | 72/x=8 | | 7=6q/4+8/4 | | 7*x=49 | | R-1/2(4R+2)=0 | | 80/x=8 | | x^3+14x^2-9x-324=0 | | 2x+x+4+x+x+x-x-3=92 | | 2(r+1)=9 | | -6.3(x+3.7)+7.65x=-1.1x-38.99 | | 2x/5=-8 | | 7x-14y=7 | | 7x+-14y=7 | | f-8-3f=37f+4 | | 3y-3=5y-5 | | f-8-3f=3-7f | | 84-3=6y+17 | | 11x=7x-20 | | 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) |